Plasma phospholipids profiling changes were associated with the therapeutic response to Roxadustat in peritoneal dialysis patients - Ya-Hui Yang; Yishakejiang Saimaiti; Yishakejiang Saimaiti; Yang Zhao; Wen Tang (Frontiers in Physiology, 2023)
Background: Elevated Phospholipids (PLs) and sphingolipid (SM) metabolism relates to with poor clinical status and adverse outcome of end-stage kidney disease patients undergoing peritoneal dialysis (PD). Studies have suggested that the use of hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI) (Roxadustat) is associated with altered lipid metabolism. Observing on how PLs and SMs changes after the HIF-PHI treatment in PD patients may help understand the possible effect of HIF-PHI on PD patients besides correcting of anemia.Materials and methods: Stable peritoneal dialysis (PD) patients treated with Roxadustat for over 3 months were included. Phospholipid and sphingolipid metabolism were measured before and after treatment.Results: 25 PD patients were included. Overall, phospholipid and sphingolipid metabolism showed a decreasing trend after HIF-PHI treatment. Levels of LysoPC (20:0), 1,2-dilinoleoyl-sn-glycero-3-phosphocholine [CisPC (DLPC) (18:2)], lysophosphatidylethanolamine (LysoPE) (14:0), and sphingomyelin (d18:1/17:0) (17:0) were significantly decreased (all p < 0.05). Further regression analyses confirmed the significant relationship between the increased of hemoglobin levels and the decrease in egg lyso PC: phosphatidylethanolamines (PE) (16:0–18:1), PE (16:0–18:2), PE (16:0–22:6), PE (18:0–20:4), PE (18:0–18:2), LysoPE (18:0), LysoPE (18:1), and phosphatidylcholine (PC) (18:1–18:0).Conclusion: This study demonstrated that phospholipid and sphingolipid metabolism decreased after administration of HIF-PHI and was associated with improvement of anemia.